Cognitive Load in English as a Foreign Language Speaking Competency of Vocational High School Students - Dewi, Putu Wia Rosita; Arimbawa, Gusti Putu Arya; Putra, Harjuli Surya; Oya, Abas; Candiasa, I Made; Susilawati, Aay (International Journal of Language Education, 2025)
This study provides an overview of the level of students’ cognitive load in learning English in vocational schools. A quantitative descriptive study uses a cross-sectional survey conducted to measure the level of cognitive load of students in learning English in vocational schools. The subjects are 69 respondents who are students from one of the private vocational schools in Denpasar City. A questionnaire with 9 Likert scales is used to measure Intrinsic Cognitive Load (ICL) and Extraneous Cognitive Load (ECL). Data are analysed with 5 category scales based on the ideal score of the instrument used. The results show that Intrinsic Cognitive Load (ICL) dominates English learning in vocational schools compared to Extraneous Cognitive Load (ECL). The percentage of cognitive load level is dominated at a high level for Intrinsic Cognitive Load (ICL) and a medium level for Extraneous Cognitive Load (ECL). Because the results of this study explain the high cognitive load of Intrinsic Cognitive Load (ICL) level, it is recommended to balance the cognitive challenge in teaching materials so as not to burden students in learning English speaking in vocational schools. Future research should aim to examine the factors that influence these differences in cognitive load levels more comprehensively in a broader context to improve generalizability.